Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Pressures on coastal biodiversity in South Africa: a cross-realm review - LR Harris; L van Niekerk; KJ Sink; AL Skowno; SP Kirkman; JB Adams; NC James; S Lamberth; DA Lemley; P Majiedt; CF MacKay; B Newman; et al. (African Journal of Marine Science, 2026)

Scaling theory of incompressible two phase flow in porous media with tensor permeabilities - S. A. Larki; K. S. Sorbie; A. Beteta; A. Skauge; E. J. Mackay (Computational Geosciences, 2026)
A recent paper from this group extended the 1955 paper by Rapoport to anisotropic systems, and gave a full analysis of this seminal work [1, 2]. Rapoport’s approach is of importance since it leads to rigorous and exact (not approximate) scaling groups and expressions for the force balances in two phase incompressible flow. This current paper describes how to extend the Rapoport scaling “shape groups” to include the anisotropic case with tensor permeabilities. When this is carried out, it is then demonstrated that, with this modification, all of the other scaling groups are the same, and exact scaling rules still apply. This is demonstrated numerically using quite complex examples where viscous fingering is occurring in the system. Rescaled cases are presented with only viscous forces, with viscous and gravity forces and with all three forces present, i.e. viscous, gravity and capillary. In addition to extending scaling theory to tensor permeabilities, we also present some novel observations on the effects of tensor permeabilities on the fingering process itself, a matter which we believe has received very little attention in the literature.

Widespread microplastic contamination in Australian soils: Sources, pathways, and environmental implications - Subharthe Samandra; Ellis S.G. Mackay; Wesam S. Alwan; Amanda V. Ellis; Bradley O. Clarke (Chemosphere, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Candidozyma auris Reported in Scotland: a Call for Vigilance Amid Global Rise - M. H. Howe; K. L. Bartie; W. G. Mackay; T. Inkster; S. Cairns; R. Kean; A. M. Bal; G. Ramage (Mycopathologia, 2026)
Candidozyma auris (formerly Candida auris ) is an emerging pathogenic yeast associated with healthcare outbreaks worldwide. Despite increasing reports across Europe, no published data have previously described cases in Scotland. Here, we report the first detections of C. auris in Scotland, as submitted to ARHAI Scotland. Eight cases (seven colonisations, one infection) were identified to date across four NHS Scotland boards, all linked to repatriation or recent hospitalisation abroad. To contextualise these findings, we reviewed publicly available literature and surveillance data for Western and Northern Europe, identifying considerable variation in case numbers and highlighting Scotland’s position among countries with the lowest reported cases. All Scottish cases were imported, underscoring the importance of targeted screening of patients with international healthcare exposure. These findings inform preparedness planning and support recommendations for strengthened surveillance to prevent onward transmission.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Predicting and assessing the impacts of COVID-19 disruption on marine science and sectors in Australia - Alistair J. Hobday; Vicki M. Walters; Robert L. Stephenson; Shane Baylis; Cindy Bessey; Fabio Boschetti; Catherine Bulman; Stephanie Contardo; Jeffrey M. Dambacher; Jemery Day; Natalie A. Dowling; Piers Dunstan; et al. (Reviews in Fish Biology and Fisheries, 2025)
By March 2020 coronavirus disease 2019 (COVID-19) was anticipated to present a major challenge to the work undertaken by scientists. This pandemic could be considered just one of the shocks that human society has had and will be likely to confront again in the future. As strategic thinking about the future can assist performance and planning of scientific research in the face of change, the pandemic presented an opportunity to evaluate the performance of marine researchers in prediction of future outcomes. In March 2020, two groups of researchers predicted outcomes for the Australian marine research sector, and then evaluated these predictions after 18 months. The self-assessed coping ability of a group experienced in ‘futures studies’ was not higher than the less-experienced group, suggesting that scientists in general may be well placed to cope with shocks. A range of changes to scientific endeavours (e.g., travel, fieldwork) and to marine sectors (e.g., fisheries, biodiversity) were predicted over the first 12–18 months of COVID-19 disruption. The predicted direction of change was generally correct (56%) or neutral (25%) for predictions related to the scientific endeavour, and correct (73%) or mixed (9%) for predictions related to sectors that are the focus of marine research. The success of this foresighting experiment suggests that the collective wisdom of scientists can be used by their organisations to consider the impact of shocks and disruptions and to better prepare for and cope with shocks. Graphical abstract Word cloud analysis of free text responses to questions about expected impact of COVID-19 on the activities associated with marine science

Reporting population size in wastewater-based epidemiology: A scoping review - Mackay Price; Bradley S. Simpson; Benjamin J. Tscharke; Fahad Ahmed; Emma L. Keller; Hannah Sussex; Melanie Kah; Katarzyna Sila-Nowicka; Andrew Chappell; Cobus Gerber; Sam Trowsdale (Science of The Total Environment, 2024)

Towards resilient, inclusive, sustainable livestock farming systems - Franco Bilotto; Matthew T. Harrison; Ronaldo Vibart; Alec Mackay; Karen M. Christie-Whitehead; Carla S.S. Ferreira; Richard S. Cottrell; Daniel Forster; Jinfeng Chang (Trends in Food Science & Technology, 2024)

Association mapping of selected oil palm germplasm reveals novel and known genomic regions influencing vegetative and bunch component traits - Norhalida Mohamed Serdari; Nik Shazana Nik Mohd Sanusi; Mustaffa Suzana; B S Jalani; Ian Mackay; Rajinder Singh; Maryam Mohamed Rehan; Maizura Ithnin (Genetic Resources and Crop Evolution, 2024)

The community of root fungi is associated with the growth rate of Norway spruce ( Picea abies ) - Leena Hamberg; Jarno Vanhatalo; Sannakajsa Velmala; Andy F. S. Taylor; John MacKay; Sébastien Caron; Fred O. Asiegbu; Risto Sievänen; Pasi Raumonen; Tuija Hytönen; Taina Pennanen (Environmental Microbiology, 2024)
Our study delved into the relationship between root‐associated fungi, gene expression and plant morphology in Norway spruce cuttings derived from both slow‐and fast‐growing trees. We found no clear link between the gene expression patterns of adventitious roots and the growth phenotype, suggesting no fundamental differences in the receptiveness to fungal symbionts between the phenotypes. Interestingly, saplings from slow‐growing parental trees exhibited a higher richness of ectomycorrhizal species and larger roots. Some ectomycorrhizal species, typically found on mature spruces, were more prevalent on saplings from slow‐growing spruces. The ericoid mycorrhizal fungus, Hyaloscypha hepaticola , showed a stronger association with saplings from fast‐growing spruces. Moreover, saplings from slow‐growing spruces had a greater number of Ascomycete taxa and free‐living saprotrophic fungi. Aboveground sapling stems displayed some phenotypic variation; saplings from fast‐growing phenotypes had longer branches but fewer whorls in their stems compared to those from the slow‐growing group. In conclusion, the observed root‐associated fungi and phenotypic characteristics in young Norway spruces may play a role in their long‐term growth rate. This suggests that the early interactions between spruces and fungi could potentially influence their growth trajectory.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Pharmacokinetic model of human exposure to ciprofloxacin through consumption of fish - Oguz Kaan Kum; Karen M. Chan; Noam Morningstar-Kywi; J. Andrew MacKay; Ian S. Haworth (Environmental Toxicology and Pharmacology, 2024)

Direct measurements of methane emissions from key facilities in Alberta's oil and gas supply chain - Hugh Z. Li; Scott P. Seymour; Katlyn MacKay; James S. Wang; Jack Warren; Luis Guanter; Daniel Zavala-Araiza; Mackenzie L. Smith; Donglai Xie (Science of The Total Environment, 2024)

Goals, challenges, and next steps in transdisciplinary fisheries research: perspectives and experiences from early-career researchers - Elizabeth A. Nyboer; Andrea J. Reid; Amanda L. Jeanson; Rachel Kelly; Mary Mackay; Jenny House; Sarah M. Arnold; Paul W. Simonin; Mary Grace C. Sedanza; Emma D. Rice; T. E. Angela L. Quiros; Andrea Pierucci; et al. (Reviews in Fish Biology and Fisheries, 2023)

Correction to: The effects of α‑lactalbumin supplementation and handgrip contraction on soleus motoneuron excitability - Karen Mackay-Phillips; Lucas B. R. Orssatto; Remco Polman; Jolieke C. Van der Pols; Gabriel S. Trajano (European Journal of Applied Physiology, 2023)

Effects of α-lactalbumin on strength, fatigue and psychological parameters: a randomised double-blind cross-over study - Karen Mackay-Phillips; Lucas B. R. Orssatto; Remco Polman; Jolieke C. Van der Pols; Gabriel S. Trajano (European Journal of Applied Physiology, 2023)

The effects of α-lactalbumin supplementation and handgrip contraction on soleus motoneuron excitability - Karen Mackay Phillips; Lucas B. R. Orssatto; Remco Polman; Jolieke C. Van der Pols; Gabriel S. Trajano (European Journal of Applied Physiology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Neutrophils in cancer—unresolved questions - Melissa S. F. Ng; Leonard Tan; Quanbo Wang; Charles R. Mackay; Lai Guan Ng (Science China Life Sciences, 2021)

On the Modelling of Immiscible Viscous Fingering in Two-Phase Flow in Porous Media - K. S. Sorbie; A. Y. Al Ghafri; A. Skauge; E. J. Mackay (Transport in Porous Media, 2020)
Viscous fingering in porous media is an instability which occurs when a low-viscosity injected fluid displaces a much more viscous resident fluid, under miscible or immiscible conditions. Immiscible viscous fingering is more complex and has been found to be difficult to simulate numerically and is the main focus of this paper. Many researchers have identified the source of the problem of simulating realistic immiscible fingering as being in the numerics of the process, and a large number of studies have appeared applying high-order numerical schemes to the problem with some limited success. We believe that this view is incorrect and that the solution to the problem of modelling immiscible viscous fingering lies in the physics and related mathematical formulation of the problem. At the heart of our approach is what we describe as the resolution of the “ M - paradox ”, where M is the mobility ratio, as explained below. In this paper, we present a new 4-stage approach to the modelling of realistic two-phase immiscible viscous fingering by (1) formulating the problem based on the experimentally observed fractional flows in the fingers, which we denote as $$ f_{\rm w}^{*} $$ f w ∗ , and which is the chosen simulation input; (2) from the infinite choice of relative permeability (RP) functions, $$ k_{\rm rw}^{*} $$ k rw ∗ and $$ k_{\rm ro}^{*} $$ k ro ∗ , which yield the same $$ f_{\rm w}^{*} $$ f w ∗ , we choose the set which maximises the total mobility function, $$ \lambda_{\text{T}}^{{}} $$ λ T (where $$ \lambda_{\text{T}}^{{}} = \lambda_{\text{o}}^{{}} + \lambda_{\text{w}}^{{}} $$ λ T = λ o + λ w ), i.e. minimises the pressure drop across the fingering system; (3) the permeability structure of the heterogeneous domain (the porous medium) is then chosen based on a random correlated field (RCF) in this case; and finally, (4) using a sufficiently fine numerical grid, but with simple transport numerics. Using our approach, realistic immiscible fingering can be simulated using elementary numerical methods (e.g. single-point upstreaming) for the solution of the two-phase fluid transport equations. The method is illustrated by simulating the type of immiscible viscous fingering observed in many experiments in 2D slabs of rock where water displaces very viscous oil where the oil/water viscosity ratio is $$ (\mu_{\text{o}} /\mu_{\text{w}} ) = 1600 $$ ( μ o / μ w ) = 1600 . Simulations are presented for two example cases, for different levels of water saturation in the main viscous finger (i.e. for 2 different underlying $$ f_{\rm w}^{*} $$ f w ∗ functions) produce very realistic fingering patterns which are qualitatively similar to observations in several respects, as discussed. Additional simulations of tertiary polymer flooding are also presented for which good experimental data are available for displacements in 2D rock slabs (Skauge et al., in: Presented at SPE Improved Oil Recovery Symposium, 14–18 April, Tulsa, Oklahoma, USA, SPE-154292-MS, 2012. 10.2118/154292-MS , EAGE 17th European Symposium on Improved Oil Recovery, St. Petersburg, Russia, 2013; Vik et al., in: Presented at SPE Europec featured at 80th EAGE Conference and Exhibition, Copenhagen, Denmark, SPE-190866-MS, 2018. 10.2118/190866-MS ). The finger patterns for the polymer displacements and the magnitude and timing of the oil displacement response show excellent qualitative agreement with experiment, and indeed, they fully explain the observations in terms of an enhanced viscous crossflow mechanism (Sorbie and Skauge, in: Proceedings of the EAGE 20th Symposium on IOR, Pau, France, 2019). As a sensitivity, we also present some example results where the adjusted fractional flow ( $$ f_{\rm w}^{*} $$ f w ∗ ) can give a chosen frontal shock saturation, $$ S_{\rm wf}^{*} $$ S wf ∗ , but at different frontal mobility ratios, $$ M(S_{\rm wf}^{*} ) $$ M ( S wf ∗ ) . Finally, two tests on the robustness of the method are presented on the effect of both rescaling the permeability field and on grid coarsening. It is demonstrated that our approach is very robust to both permeability field rescaling, i.e. where the ( k max / k min ) ratio in the RCF goes from 100 to 3, and also under numerical grid coarsening.

Increased reproductive success through parasitoid release at a range margin: Implications for range shifts induced by climate change - K. David Mackay; Caroline L. Gross; Darren S. Ryder (Journal of Biogeography, 2020)
Aim We tested four hypotheses (a) that pioneer trees at distribution margins would receive fewer visits from pollinators and pollinator parasitoids than would trees in larger, established populations; (b) that predator release (lower rates of pollinator parasitism) would result in higher pollinator reproductive success; (c) that less competition among fewer pollinator foundresses would correlate with higher plant reproductive success and (d) that these effects would be greater at the plant species’ expanding range margin. Location The dry, western side of the Great Dividing Range in northern New South Wales, eastern Australia. Taxon The rusty fig ( Ficus rubiginosa, Moraceae), its pollinator and the pollinator's parasitoids. Methods We measured fruit (syconia) set per tree, seed set per syconium and fig‐wasp numbers (pollinators and non‐pollinators) per syconium in a total of 62 trees in 24 populations covering three distributional zones – the dry, western margin of the species’ range, a more mesic, eastern margin at the species’ altitudinal limit, and the zone between these two margins. These results were modelled against F. rubiginosa population size, the position of plant populations in relation to range margins, and climatic gradients of temperature and rainfall. Results Lower rates of pollinator parasitism and less pollinator competition correlated with increased reproductive success in the pollinator and increased male fitness (in terms of pollen dispersal) and female fitness (in terms of seed per syconium) in isolated trees of F. rubiginosa , compared with trees in larger populations, particularly at F. rubiginosa's mesic, expanding range margin. Main Conclusions Pollinator–predator release and pollinator–competition release can lead to increased pollinator and plant reproductive success in pioneer trees at range margins. This reinforces the need to understand biotic interactions underlying reproduction and dispersal at expanding range fronts if we are to understand and better predict the drivers and effects of climate‐change‐induced range shifts in plants and their pollinators.

Detailed Assessment of Compositional and Interfacial Tension Effects on the Fluid Behaviour During Immiscible and Near-Miscible CO2 Continuous and WAG Displacements - Gang Wang; Gillian E. Pickup; Kenneth S. Sorbie; Eric J. Mackay (Transport in Porous Media, 2020)
This study seeks to improve numerical simulations of the key physics occurring in CO 2 enhanced oil recovery (CO 2 -EOR) processes, with a particular focus on the transition from immiscible to miscible displacements. In the previous work, we have investigated interactions between compositional effects and the underlying heterogeneities of the flow field in near-miscible floods (Wang et al. in Transp Porous Media 129(3):743–759, 2019a). In this current study, we have further analysed the effects of reduction in interfacial tension (IFT) on the flow behaviour, as motivated by the study on the film-flow mechanism previously presented by Sorbie and van Dijke (SPE improved oil recovery symposium, Society of Petroleum Engineers, 2010). We identify two clear mechanisms of oil recovery that may occur in near-miscible CO 2 (or other gas) injection processes, which we denote, M CE , as oil stripping or conventional compositional effects, and M IFT as lower IFT oil film-flow effects. The latter M IFT effects are described by an enhanced hydrocarbon relative permeability in the near-miscible three-phase relative permeabilities (3PRP). Various combinations between the M CE and M IFT mechanisms were tested by numerical simulations to evaluate the impact of each mechanism on the flow behaviour, i.e. their separate and joint effects on quantities such as the local oil displacement efficiency, phase flow vectors and the ultimate oil recovery. When acting in combination, the oil stripping and IFT effects can greatly improve the local displacement performance even when viscous fingering flow occurs. Viscous fingering is well known to lead to bypassed oil in the “non-preferential” flow paths between the main fingers. We show that the remaining oil in these non-preferential flow paths (i.e. bypassed oil) can be efficiently recovered by the combined M CE and M IFT mechanisms, but only with the application of water alternating gas (WAG). In contrast to oil stripping effects, the IFT effect is not dependent on continuous contact between oil and CO 2 . Instead, the remaining oil is mobilized by gas as the IFT is reduced and can be efficiently produced by subsequent water injection. This M IFT mechanism has much less impact in cases with continuous CO 2 injection compared to its efficiency in WAG. This is because during continuous injection, gas fingers are dominant in the preferential flow paths, and therefore the local displacement efficiency is very good, but only in these preferential routes. On the other hand, WAG is able to make full use of the IFT effects because of its relatively stable displacing front, which allows the M IFT mechanism to contribute. In this study, the effects of using different three-phase relative permeability methods were investigated and, as expected, different methods yielded different results. However, an important observation is that when IFT effects ( M IFT ) were included, there was much less difference in the final oil recovery using the different 3PRP models; our analysis shows why this is the case.

Interactions between two species of recently-sympatric invasive honeybees: Apis cerana induces aggression in Apis mellifera during foraging - C. L. Gross; J. D. Whitehead; E. S. G. Mackay; K. D. Mackay; N. R. Andrew; D. Paini (Biological Invasions, 2019)

Variance in the response of silcrete to rapid heating complicates assumptions about past heat treatment methods - Alex Mackay; Sam C. Lin; Lachlan S. Kenna; Alex F. Blackwood (Archaeological and Anthropological Sciences, 2019)

Analysis of Compositional Effects on Global Flow Regimes in CO2 Near-Miscible Displacements in Heterogeneous Systems - G. Wang; G. E. Pickup; K. S. Sorbie; E. J. Mackay (Transport in Porous Media, 2019)

Ten tips for developing interdisciplinary socio-ecological researchers - Rachel Kelly; Mary Mackay; Kirsty L. Nash; Christopher Cvitanovic; Edward H. Allison; Derek Armitage; Aletta Bonn; Steven J. Cooke; Stewart Frusher; Elizabeth A. Fulton; Benjamin S. Halpern; Priscila F. M. Lopes; et al. (Socio-Ecological Practice Research, 2019)

Bacteria and viruses in the nasopharynx immediately prior to onset of acute lower respiratory infections in Indigenous Australian children - Heidi C. Smith-Vaughan; Michael J. Binks; Jemima Beissbarth; Anne B. Chang; Gabrielle B. McCallum; Ian M. Mackay; Peter S. Morris; Robyn L. Marsh; Paul J. Torzillo; Danielle F. Wurzel; Keith Grimwood; Elizabeth Nosworthy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Spatial differences in dissolved silicon utilization in Lake Baikal, Siberia: Examining the impact of high diatom biomass events and eutrophication - V. N. Panizzo; S. Roberts; G. E. A. Swann; S. McGowan; A. W. Mackay; E. Vologina; V. Pashley; M. S. A. Horstwood (Limnology and Oceanography, 2018)
Recent research has highlighted how Lake Baikal, Siberia, has responded to the direct and indirect effects of climate change (e.g., ice‐cover duration), nutrient loading, and pollution, manifesting as changes in phytoplankton/zooplankton populations, community structure, and seasonal succession. Here, we combine and compare analyses of chlorophyll a (an estimate of total algal biomass), carotenoid pigments (biomarkers of algal groups), and lake water silicon isotope geochemistry (δ 30 Si DSi ) to differentiate spatial patterns in dissolved silicon (DSi) uptake at Lake Baikal. A total of 15 sites across the three basins (south, central, and north) of Lake Baikal were sampled in August 2013 along a depth gradient of 0–180 m. Strong, significant correlations were found between vertical profiles of photic zone DSi concentrations and δ 30 Si DSi compositions ( r = −0.81, p r = −0.98, p 30 Si DSi compositions suggest greater productivity in the south basin and more oligotrophic conditions in the north basin. δ 30 Si DSi signatures are highest at depth (20 m) in central basin sites, indicating greater (10–40%) DSi utilization at deep chlorophyll maxima. DSi limitation occurs in the pelagic central basin, probably reflecting a high diatom biomass bloom event ( Aulacoseira baicalensis ). Meanwhile in the more hydrologically restricted, shallow Maloe More region (central basin), both high δ 30 Si DSi compositions and picocyanobacteria (zeaxanthin) concentrations, respectively point to the legacy of an “ Aulacoseira bloom year” and continuous nutrient supply in summer months (e.g., localized eutrophication).

Correction to: Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Evaluation of phosphorus in thermally converted sewage sludge: P pools and availability to wheat - Jessica E. Mackay; Timothy R. Cavagnaro; Iver Jakobsen; Lynne M. Macdonald; Mette Grønlund; Tobias P. Thomsen; Dorette S. Müller-Stöver (Plant and Soil, 2017)

New Zealand collections of Rhododendron as a resource for ex situ conservation - M. B. MacKay; G. F. Smith; S. E. Gardiner (New Zealand Journal of Botany, 2017)
This study uses Rhododendron L. collections in New Zealand to analyse the contribution of introduced species in cultivation to global ex situ conservation. Living botanical collections of Red List taxa are the fundamental resource that enable ex situ conservation, and Target 8 of the Global Strategy for Plant Conservation requires 75% of Red List taxa to be in ex situ collections by 2020. We compared Rhododendron taxa (species, subspecies, botanical varieties) in New Zealand with the range of taxa in international cultivation, and determined the presence of taxa from Red List categories, geographic origins and taxonomic groups. The 566 taxa in New Zealand, including 224 Red List taxa, encompass 67% of the taxa in cultivation worldwide, ranking second internationally for number of taxa in the collections investigated. New Zealand holds wild‐collected material of 230 taxa, including 70 Red List taxa, and 20 taxa for which wild material is not listed in the international collections studied. China is the geographic origin of the greatest number of Rhododendron Red List taxa held in New Zealand. Of the 77 taxonomic subsections of Rhododendron , New Zealand holds 75% or more of the taxa in cultivation for 37 subsections, and 75% or more of the Red List taxa in cultivation for 24 subsections. The greatest numbers of Red List taxa in New Zealand collections are from section Rhododendron subsection Maddenia (20) and section Pontica subsection Neriiflora (17). Our analysis enables us to (1) propose conservation action for Rhododendron in New Zealand, (2) summarise our approach as a model for examining other introduced plant genera in New Zealand, and (3) propose our method as a component of an ex situ conservation strategy for New Zealand.

Kathleen Schwerdtner Máñez and Bo Poulsen (eds): Perspectives on oceans past: a handbook of marine environmental history - Rachel Kelly; Richard S. Cottrell; Mary Mackay; Yannick Rousseau (Reviews in Fish Biology and Fisheries, 2017)

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Optimising gut colonisation resistance against Clostridium difficile infection - S. Yuille; W. G. Mackay; D. J. Morrison; M. C. Tedford (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Pore-to-Core-Scale Network Modelling of $$CO_{2}$$ CO 2 Migration in Porous Media - U. Bagudu; S. R. McDougall; E. J. Mackay (Transport in Porous Media, 2015)

The Changing Cold Regions Network: Observation, diagnosis and prediction of environmental change in the Saskatchewan and Mackenzie River Basins, Canada - Chris M. Debeer; Howard S. Wheater; William L. Quinton; Sean K. Carey; Ronald E. Stewart; Murray D. MacKay; Philip Marsh (Science China Earth Sciences, 2015)

A reassessment of late glacial – Holocene diatom oxygen isotope record from Lake Baikal using a geochemical mass‐balance approach - Anson W. Mackay; George E. A. Swann; Tim S. Brewer; Melanie J. Leng; David W. Morley; Natalia Piotrowska; Patrick Rioual; Dustin White (Journal of Quaternary Science, 2011)
We present a new palaeoenvironmental record of hydrological variability in Lake Baikal, based on re‐modelled δ 18 O diatom values of diatom silica (δ 18 O modelled ), where the residual contaminants are identified and compensated for using electron optical imaging and whole‐sample geochemistry. δ 18 O modelled interpretations are based on the balance between rivers with high δ 18 O values and rivers with low δ 18 O values. Isotopic variability is related to latitudinal differences in precipitation which feed these rivers. The δ 18 O modelled record suggests that rather moist conditions prevailed in the Lake Baikal region during the latter stages of the Younger Dryas. Throughout the Holocene, episodes of low δ 18 O modelled values are, in general, in good agreement with increases in percentage haematite‐stained grains in North Atlantic sediments (indicative of ice‐rafted debris events). Rivers with southerly catchments dominate fluvial input especially between c . 3.3 and 2 cal ka BP, concurrent with high precipitation in the Lake Baikal region. Copyright © 2011 John Wiley & Sons, Ltd.

External quality assessment of the molecular diagnostics and genotyping of meticillin-resistant Staphylococcus aureus - R. te Witt; A. van Belkum; W. G. MacKay; P. S. Wallace; W. B. van Leeuwen (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Modeling lakes and reservoirs in the climate system - M. D. MacKay; P. J. Neale; C. D. Arp; L. N. De Senerpont Domis; X. Fang; G. Gal; K. D. Jöhnk; G. Kirillin; J. D. Lenters; E. Litchman; S. MacIntyre; P. Marsh; et al. (Limnology and Oceanography, 2009)
Modeling studies examining the effect of lakes on regional and global climate, as well as studies on the influence of climate variability and change on aquatic ecosystems, are surveyed. Fully coupled atmosphere‐land surface‐lake climate models that could be used for both of these types of study simultaneously do not presently exist, though there are many applications that would benefit from such models. It is argued here that current understanding of physical and biogeochemical processes in freshwater systems is sufficient to begin to construct such models, and a path forward is proposed. The largest impediment to fully representing lakes in the climate system lies in the handling of lakes that are too small to be explicitly resolved by the climate model, and that make up the majority of the lake‐covered area at the resolutions currently used by global and regional climate models. Ongoing development within the hydrological sciences community and continual improvements in model resolution should help ameliorate this issue.

Pyruvate dehydrogenase phosphatase 1 (PDP1) null mutation produces a lethal infantile phenotype - J. M. Cameron; M. Maj; V. Levandovskiy; C. P. Barnett; S. Blaser; N. MacKay; J. Raiman; A. Feigenbaum; A. Schulze; B. H. Robinson (Human Genetics, 2009)

Over‐summering behaviour of Atlantic salmon Salmo salar returning to rivers in the Cromarty Firth, north–east Scotland - D. C. Stewart; S. J. Middlemas; S. Mackay; J. D. Armstrong (Journal of Fish Biology, 2009)
In 2005, a high percentage (50%) of Atlantic salmon Salmo salar fitted with acoustic transmitters, which entered rivers in the Cromarty Firth area of north–east Scotland dropped back to the estuary and ascended adjacent rivers after 33–80 days of freshwater residence. Fish residing in non‐natal rivers generate mixed stock fisheries, and movements of fish between rivers could increase the risk of disease transmission between catchments.

Habitat use and dispersal of post‐smolt sea trout Salmo trutta in a Scottish sea loch system - S. J. Middlemas; D. C. Stewart; S. Mackay; J. D. Armstrong (Journal of Fish Biology, 2009)
Post‐smolt anadromous brown trout Salmo trutta , sea trout, from two Scottish west coast rivers, the Balgy and Shieldaig, flowing into adjacent sea lochs were tracked simultaneously using arrays of moored acoustic receivers to determine dispersal patterns and loss rates. Fish tended to stay close to their natal rivers for the first 14 day after entering the sea, during which time about half the fish were lost to the study. Although initially the overall pattern of dispersal was similar for individual fish from both rivers, towards the end of the study the groups had converged into one of the loch basins. There were also pronounced individual differences in habitat use with all those fish detected for >42 days exhibiting different patterns of habitat use. Loss rates were similar between the two rivers despite differences in the range of air‐breathing predators to which the fish were initially exposed. These findings suggest that any management of predators or other mortality agents should be targeted towards mouths of rivers during and immediately following smolt emigration.

Unravelling contamination signals in biogenic silica oxygen isotope composition: the role of major and trace element geochemistry - Tim S. Brewer; Melanie J. Leng; Anson W. Mackay; Angela L. Lamb; Jonathan J. Tyler; Nicholas G. Marsh (Journal of Quaternary Science, 2008)
The oxygen isotope composition of diatom silica ( δ 18 O diatom ) provides valuable information for palaeoclimate studies where carbonate proxies are either rare or absent in many lakes and ocean sediments. Unfortunately, mineral and rock fragments found alongside diatoms in most sediments can be problematic as the method used will liberate oxygen from all components within the sediment, producing both high‐frequency noise and low‐frequency excursions that can resemble climate signals. Removal of mineral contamination to date has largely relied upon the combination of chemical leaching and physical separation techniques (e.g. sieving, density). This combination can be inefficient and often significant proportions of contaminants are present in the ‘purified’ diatom sample. Using electron optical imaging and whole‐rock geochemistry on previously ‘purified’ diatom samples, a mass balance approach has been developed whereby the types and proportions of residual contaminants are identified. By integrating this information with measured oxygen isotope ratios of the contaminants, it is then possible to remove contamination effects from the δ 18 O diatom record. Contamination effects relating to carbonates, tephra and silt are modelled for cores from Lake Tilo (Ethiopia) and Lake Baikal (Siberia). In both lakes the new modelled δ 18 O diatom curves show less high‐frequency noise, thus enabling better resolution of low‐frequency climate signals. © Natural Environment Research Council (NERC) copyright 2008. Reproduced with the permission of NERC. Published by John Wiley & Sons Ltd.

The genetic diversity of UK, US and Australian cultivars of Triticum aestivum measured by DArT markers and considered by genome - J. White; J. R. Law; I. MacKay; K. J. Chalmers; J. S. C. Smith; A. Kilian; W. Powell (Theoretical and Applied Genetics, 2008)

Can thin-billed prions Pachyptila belcheri breed successfully on an island with introduced rats, mice and cats? The case of New Island, Falkland Islands - P. Catry; M. C. Silva; S. MacKay; A. Campos; J. Masello; P. Quillfeldt; I. J. Strange (Polar Biology, 2007)

Development and Application of a Predictive Model of Freshwater Fish Assemblage Composition to Evaluate River Health in Eastern Australia - M. J. Kennard; B. J. Pusey; A. H. Arthington; B. D. Harch; S. J. Mackay (Hydrobiologia, 2006)

A maternal hypomethylation syndrome presenting as transient neonatal diabetes mellitus - D. J. G. Mackay; S. E. Boonen; J. Clayton-Smith; J. Goodship; J. M. D. Hahnemann; S. G. Kant; P. R. Njølstad; N. H. Robin; D. O. Robinson; R. Siebert; J. P. H. Shield; H. E. White; et al. (Human Genetics, 2006)

Epimutation of the TNDM locus and the Beckwith–Wiedemann syndrome centromeric locus in individuals with transient neonatal diabetes mellitus - D. J. G Mackay; J. M. D. Hahnemann; S. E. Boonen; S. Poerksen; D. J. Bunyan; H. E. White; V. J. Durston; N. S. Thomas; D. O. Robinson; J. P. H Shield; J. Clayton-Smith; I. K. Temple (Human Genetics, 2006)

Genetic control of somatic embryogenesis initiation in loblolly pine and implications for breeding - J. J. MacKay; M. R. Becwar; Y. -S. Park; J. P. Corderro; G. S. Pullman (Tree Genetics & Genomes, 2006)

Variation in Wood Density and Shrinkage and Their Relationship to Growth of Selected Young Poplar Hybrid Crosses - Alfas Pliura; Qibin Yu; S. Y. Zhang; John MacKay; Pierre Périnet; Jean Bousquet (Forest Science, 2005)
Wood density, various shrinkages and several growth traits were measured in two 10-year-old clonal trials at sites of contrasting growth potential. The material studied consisted of 12 clones of three poplar hybrid crosses, Populus deltoides × P. nigra, P. trichocarpa × P. deltoides, and P. maximowiczii × P. balsamifera, as well as P. deltoides. Wood density and longitudinal and radial wood shrinkages were significantly lower at the St-Ours than at the Windsor site, by 6.7, 46.7, and 14.9%, respectively, while growth rate was increased. The differences among hybrid crosses were significant for all growth traits and wood properties except for radial and tangential shrinkages of juvenile wood. P. deltoides had the highest wood density of 363.2 kg/m3, whereas P. maximowiczii × P. balsamifera wood had the lowest density of 299.8 kg/m3. The differences among hybrid crosses were significant for growth traits, primarily due to the fast growth of P. trichocarpa × P. deltoides and slow growth of P. deltoides. Among the wood properties measured, only tangential wood shrinkage exhibited clear radial intertree changes with cambial age. The tangential wood shrinkage increased from pith to mid-diameter and then started to decrease outward, with each hybrid showing a different pattern of variation. Phenotypic clonal mean correlations among growth traits and wood density were weakly negative. Correlations among growth traits and radial wood shrinkage ranged from weakly to strongly negative. Longitudinal shrinkage displayed strong negative correlations with radial and tangential shrinkages. Negative correlations found between wood density and longitudinal shrinkage and positive correlations between density and both radial and tangential shrinkages suggest that selection for high wood density may lead to increased transverse wood shrinkage but decreased longitudinal shrinkage. FOR. SCI. 51(5):472–482.

Monozygous triplets discordant for transient neonatal diabetes mellitus and for imprinting of the TNDM differentially methylated region - S. G. Kant; A. M. van der Weij; W. Oostdijk; J. M. Wit; D. O. Robinson; I. K. Temple; D. J. G. Mackay (Human Genetics, 2005)

Overlapping gene expression profiles in rheumatoid fibroblast-like synoviocytes induced by the proinflammatory cytokines interleukin-1 ? and tumor necrosis factor - M. Taberner; K. F. Scott; L. Weininger; C. R. Mackay; M. S. Rolph (Inflammation Research, 2005)

Formation of platinated GG cross-links on DNA by photoactivation of a platinum(IV) azide complex - Jana Kašpárková; Fiona S. Mackay; Viktor Brabec; Peter J. Sadler (JBIC Journal of Biological Inorganic Chemistry, 2003)

Effects of aggregated classifications of forest composition on estimates of evapotranspiration in a northern Wisconsin forest - D. S. MACKAY; D. E. AHL; B. E. EWERS; S. T. GOWER; S. N. BURROWS; S. SAMANTA; K. J. DAVIS (Global Change Biology, 2002)
Forest management presents challenges to accurate prediction of water and carbon exchange between the land surface and atmosphere, due to its alteration of forest structure and composition. We examined how forest species types in northern Wisconsin affect landscape scale water fluxes predicted from models driven by remotely sensed forest classification. A site‐specific classification was developed for the study site. Using this information and a digital soils database produced for the site we identified four key forest stand types: red pine, northern hardwoods, aspen, and forested wetland. Within these stand types, 64 trees representing 7 species were continuously monitored with sap flux sensors. Scaled stand‐level transpiration from sap flux was combined with a two‐source soil evaporation model and then applied over a 2.5 km × 3.0 km area around the WLEF AmeriFlux tower (Park Falls, Wisconsin) to estimate evapotranspiration. Water flux data at the tower was used as a check against these estimates. Then, experiments were conducted to determine the effects of aggregating vegetation types to International Geosphere– Biosphere Program (IGBP) level on water flux predictions. Taxonomic aggregation resulting in loss of species level information significantly altered landscape water flux predictions. However, daily water fluxes were not significantly affected by spatial aggregation when forested wetland evaporation was included. The results demonstrate the importance of aspen, which has a higher transpiration rate per unit leaf area than other forest species. However, more significant uncertainty results from not including forested wetland with its high rates of evaporation during wet summers.

Numerical Simulation of the Movement of Saltwater under Skimming and Scavenger Pumping in the Pleistocene Aquifer of Gaza and Jericho Areas, Palestine - A. S. Aliewi; R. Mackay; A. Jayyousi; K. Nasereddin; A. Mushtaha; A. Yaqubi (Transport in Porous Media, 2001)

Sustaining potato crop, land and industry health beyond the year 2000: Current issues and future needs - H. W. (Bud) Platt; E. S. Plissey; G. R. MacKay; M. Adams; M. K. Hinkle; E. MacDonald (American Journal of Potato Research, 2000)

Controlling leucine zipper specificity with interfacial hydrophobic residues - Naresh P. S. Bains; Jackie A. Wilce; Lindsey G. Mackay; Glenn F. King (International Journal of Peptide Research and Therapeutics, 1999)

Average effect of a mutation in lignin biosynthesis in loblolly pine - R. L. Wu; D. L. Remington; J. J. MacKay; S. E. McKeand; D. M. O’Malley (Theoretical and Applied Genetics, 1999)

Connexin 50 mutation in a family with congenital "zonular nuclear" pulverulent cataract of Pakistani origin - Vanita Berry; Donna Mackay; Shagufta Khaliq; Peter J. Francis; Abdul Hameed; Khalid Anwar; S. Qasim Mehdi; Richard J. Newbold; Alex Ionides; Alan Shiels; Tony Moore; Shomi S. Bhattacharya (Human Genetics, 1999)

The genetics of selfing with concurrent backcrossing in breeding hybrid sugar beet (Beta vulgaris altissima L.) - I. J. Mackay; J. P. Gibson; P. D. S. Caligari (Theoretical and Applied Genetics, 1999)

Differentiation of infection from vaccination in foot-and-mouth disease by the detection of antibodies to the non-structural proteins 3D, 3AB and 3ABC in ELISA using antigens expressed in baculovirus - K. J. Sørensen; K. G. Madsen; E. S. Madsen; J. S. Salt; J. Nqindi; D. K. J. Mackay (Archives of Virology, 1998)

Viruses produced from complementary DNA of virulent and avirulent strains of swine vesicular disease viruses retain the in vivo and in vitro characteristics of the parental strain - T. Kanno; T. Inoue; D. Mackay; P. Kitching; S. Yamaguchi; J. Shirai (Archives of Virology, 1998)

Partitioning and translocation of photosynthetically fixed 14 C in grazed hill pastures - S. Saggar; C. Hedley; A. D. Mackay (Biology and Fertility of Soils, 1997)